Relationship between Cycling Mileage and VO2max Value of Cyclists in Bike Community Mataram City, West Nusa Tenggara - Ida Ayu Eka Widiastuti; Rifana Cholidah; Gede Wira Buanayuda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Currently cycling is a sport that is in vogue. Exercise that is done regularly and programmed will improve physical fitness, which can be seen from the maximum oxygen uptake (VO2max.). This study aims to determine the relationship between cycling distance and VO2max. value achievement on cyclists who are members of the bicycle community in Kota Mataram, Nusa Tenggara Barat. This research is an observational analytic study with cross sectional method. The research subjects were 34 cyclists from 5 bicycle communities in Kota Mataram, who were determined by non-probability sampling technique, namely consecutive sampling. VO2max. measurement, carried out by loading tests using the Bruce Protocol, while the cycling distance is obtained from the data recorded on the Strava application. The results showed that the mean VO2max. value of the subjects was 37.51 ml / kg / minute and the mean distance traveled by cycling was 4256.53 km. Correlative analysis using Spearman, obtained the value of r = 0.406 with p = 0.017. There is a significant correlation between cycling distance and VO2max. value with moderate correlation strength.